Effects of continuous exposure to power frequency electric fields on soybean Glycine max. (August 2019) - Li, Xiang; Liu, Xingfa; Wan, Baoquan; Li, Xiangwen; Li, Mengyu; Zhu, Hongyuan; Hua, Hongxia
Abstract: With the increasing density of high voltage transmission systems, the potential risks and hazards of environmental electric fields (EFs) generated by these systems to surrounding organisms is becoming a source of public concern. To evaluate the effect of environmental EFs on plants, we used soybean as a model and systematically evaluated the effect of continuous exposure to different intensities (0 kV/m, 2 kV/m, and 10 kV/m) of power frequency EFs on agronomic characters, yield, nutrient contents, protective enzyme activities, and gene transcription. We found that the effects on soybean were more pronounced when plants were exposed to EF during development (especially at the seedling stage) than when they were exposed at maturity. The functional leaf number, stem diameter, plant dry weight, and pod number were largely unaffected by EF, while the germination rate and protective enzyme activities increased with increasing EF intensity. In plants exposed to low-intensity EF (2 kV/m), some agronomic characters, including chlorophyll content, plant height, and bean dry weight, as well as the soluble sugar and total protein contents, were significantly higher than those of plants exposed to high-intensity EF (10 kV/m) and control plants (0 kV/m). Through transcriptome analysis, we found that 2, 977 genes were significantly up-regulated and 1, 462 genes were down-regulated when plants were exposed to EF. These differentially expressed genes mainly encode ribosome proteins and related enzymes involved in carbon metabolism pathway, providing a novel perspective for understanding molecular mechanisms underpinning the responses to EF stress in soybean. Graphical abstract: Image 1 Highlights: EF generated by high-voltage transmission line may have ecological impact. Low-intensity EF shown to increase photosynthesis efficiency and soybean yield. EF treatment shown to increase the protective enzyme activity of soybean. Differentially expressed genes induced by EF mainly encode ribosome proteins and carbon metabolism enzymes.